FOREIGN ANALYSIS OF USING DIGITAL EDUCATIONAL TOOLS IN TEACHING THE MOTHER TONGUE TO PRIMARY SCHOOL STUDENTS - Kurbanova Gulshan Berdimurodovna (Sciental Journals Publishing, 2026)
This article deeply studies foreign experiences in teaching the mother tongue in primary grades based on digital educational tools and analyzes their pedagogical effectiveness. Digital platforms, interactive programs, multimodal educational resources, adaptive learning systems, and artificial intelligence-based teaching technologies used in schools in countries with developed education systems in the world, Finland, South Korea, Singapore, Estonia, and the United States, were studied. The analysis of foreign experiences made it possible to identify factors that contribute to the individualization of mother tongue teaching in primary education, the involvement of students in active learning practices, and the effective management of the learning process. The article also highlights the existing opportunities and integration directions in the use of digital tools in the education system of Uzbekistan based on a comparative analysis.
Keywords: digital education, primary school, native language, foreign experience, interactive platform, digital pedagogy, artificial intelligence, multimodal resources, educational technologies, adaptive learning systems, competency approach.